Current and Recent Advanced Strategies for Combating Biofilms. Issue 4 (July 2015) - Sadekuzzaman, M.; Yang, S.; Mizan, M.F.R.; Ha, S.D.
Abstract Biofilms are matrix‐enclosed microbial aggregates that adhere to a biological or nonbiological surface. Biofilm formation is a significant problem in the medical, food, and marine industries and can lead to substantial economic and health problems. The complex microbial community of a biofilm is highly resistant to antibiotics and sanitizers and confers persistent survival that is a challenge to overcome. There are several conventional approaches to combating biofilms, physical and/or mechanical removal, chemical removal, and the use of antimicrobials, sanitizers, or disinfectants to kill biofilm organisms. However, biofilms are highly resistant to these approaches as opposed to planktonic cells. Thus, novel approaches other than the conventional methods are urgently needed. In this review, we discuss current and new advanced antibiofilm strategies that are superior to the conventional method in terms of addressing the biofilm problem for the improvement of healthcare, food safety, and in industrial processes.